Management of associated anomalies of oesophageal atresia and tracheo-oesophageal fistula - Kamalesh Pal (Wolters Kluwer Medknow Publications, 2014)
Tracheo-oesophageal fistula (TEF)/oesophageal atresia is one of the most common and serious congenital malformation. Despite progresses made in the field of early diagnosis, surgical techniques, ventilatory support and control of chest infections; morbidity and mortality still remains quite high and differs a lot from one to another centre particularly in the developing countries; as the availability and the level of neonatal care facilities are different. Associated anomalies play a significant role in dictating the outcome, timing of intervention and even the approach to management. The objectives of this review article is to outline the spectrum of associated anomalies, emphasise need of standardised system of documentation of anomalies, prognosis and management issues that would influence timing and approach of TEF repair.